2012
DOI: 10.3109/10408444.2011.636342
|View full text |Cite
|
Sign up to set email alerts
|

A reassessment of risk associated with dietary intake of ochratoxin A based on a lifetime exposure model

Abstract: Mycotoxins, such as ochratoxin A (OTA), can occur from fungal growth on foods. OTA is considered a possible risk factor for adverse renal effects in humans based on renal tumors in male rats. For risk mitigation. Health Canada proposed maximum limits (MLs) for OTA based largely on a comparative risk assessment conducted by Health Canada (Kuiper-Goodman et al., 2010), in which analytical data of OTA in foods were used to determine the possible impact adopting MLs may have on OTA risks. The EU MLs were used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 100 publications
1
19
0
Order By: Relevance
“…The use of a reference dose from a cancer endpoint of a non-genotoxic carcinogen that is considered a threshold carcinogen, like OTA, requires the assumption that risk associated with an acute dose is equivalent to low dose spread over time (Waddell, 2006; Haighton et al 2012). Due to uncertainty in intermittent or varying levels of exposure experienced by humans over a lifetime, the US EPA has recommended calculating lifetime average daily dose (EPA 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a reference dose from a cancer endpoint of a non-genotoxic carcinogen that is considered a threshold carcinogen, like OTA, requires the assumption that risk associated with an acute dose is equivalent to low dose spread over time (Waddell, 2006; Haighton et al 2012). Due to uncertainty in intermittent or varying levels of exposure experienced by humans over a lifetime, the US EPA has recommended calculating lifetime average daily dose (EPA 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, use of a NCRI value based on a non-threshold carcinogenicity theory could be overestimating the risk for human carcinogenesis. For instance, Haighton et al (2012) revisited this risk assessment as well as the EFSA assessment and concluded that the most plausible toxicological mechanism of OTA did not involve genotoxicity, but rather, a threshold (below which no risk of renal cancer would be expected); and found the risk to the Canadian population of OTA-related cancer negligible.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, when the point estimate is used for risk assessment, the variability and uncertainty of the food consumption and the contamination levels are not considered, resulting in the overestimation of the real exposure (Haighton et al, 2012;Han et al, 2010). To account for the abovementioned shortcomings, a full probabilistic model (Monte Carlo simulation) is recommended (Nakatani et al, 2011) as was the case in this study.…”
Section: Probabilistic Analysismentioning
confidence: 95%
“…The International Agency for Research on Cancer (IARC) has classified OTA as a Group 2B possible human carcinogen, based on demonstrated carcinogenicity in animal studies (Fazekas et al, 2005; IARC, 1993), although OTA-related carcinogenicity has not been conclusively determined in humans. A recent risk assessment on OTA (Haighton et al, 2012) states that OTA was negative in genotoxicity assays with high specificity, and that OTA-DNA adduct levels were low and not typical of genotoxic carcinogens.…”
Section: Introductionmentioning
confidence: 99%